Role of agro-management techniques in reducing the immature phase of natural rubber cultivation - George, Sherin; Meti, Shankar; Idicula, Sabu P. (Journal of Plantation Crops, 2013)
The lengthy gestation period of rubber is the major deterrent factor for the rubber growers to take up new planting and replanting. The effect of different agro-management practices on enhancing the growth and thereby reducing the immaturity period of rubber (clone RRII 105) was evaluated individually and in combination (integrated management) in a field experiment conducted at Malankara estate, Thodupuzha, representing the traditional rubber growing region in India. The treatments comprised of current recommended practice, irrigation, enhanced nutrient application, selective manuring, conservation-oriented tillage, irrigation + enhanced nutrient application and integrated management which included irrigation, enhanced nutrient application, selective manuring and conservation-oriented tillage. The results of the experiment indicated that the growth of the plants under integrated management was significantly superior to others throughout the experimental phase followed by the treatments irrigation + enhanced nutrient application and irrigation which were on par. The effect of different agro-management practices was also reflected in leaf area index (LAI). The mean LAI recorded at different times was the highest for integrated management followed by irrigation + enhanced nutrient application and irrigation which were comparable. The soil moisture storage during summer also followed a similar trend. All these improved agricultural practices contributed towards the increased growth of the plants under integrated management and 72 per cent of the trees achieved tappable girth in a period of five years and nine months compared to the normal gestation period of seven years in the traditional belt. The results of the experiment clearly indicate the feasibility of substantially reducing the immaturity period through the adoption of improved agro-management techniques.